Beta-Cryptoxanthin, Plentiful in Japanese Mandarin Orange, Prevents Age-Related Cognitive Dysfunction and Oxidative Damage in Senescence-Accelerated Mouse Brain - Unno, Keiko; Sugiura, Minoru; Sakuma, Midori; Maeda, Ken-ichi; Hoshino, Minoru; Miyazaki, Hideaki; Takabayashi, Fumiyo; Yamamoto, Hiroyuki; Fujitani, Keisuke; Ogawa, Kazunori; Toda, Masateru (Biological & Pharmaceutical Bulletin, 2011)
Increased oxidative stress is known to accelerate age-related pathologies. Beta-cryptoxanthin (β-CRX, (3R)-β,β-caroten-3-ol) is a potent antioxidant that is highly rich in Satsuma mandarin orange (mandarin), which is the most popular fruit in Japan. We investigated the antioxidative and anti-aging effects of β-CRX and mandarin using senescence-accelerated mice (SAMP10), which were characterized by a short lifespan, high generation of superoxide anions in the brain and poor learning ability with aging. β-CRX (0.5—5.0 μg/ml) or mandarin juice (3.8—38.0%) was added to drinking water of SAMP10 one to 12 months of age. β-CRX was dose-dependently incorporated into the cerebral cortex and the contents were similar to the concentration of β-CRX in the human frontal lobe. These mice also had higher learning ability. The level of DNA oxidative damage was significantly lower in the cerebral cortex of mice that ingested β-CRX and mandarin than control mice. In addition, the mice that ingested β-CRX (>1.5 μg/ml) and mandarin (>11.3%) exhibited a higher survival when 12 month-old, the presenile age of SAMP10, than control mice. These results suggest that β-CRX is incorporated into the brain and has an important antioxidative role and anti-aging effect.